A development of Time Domain Reflectometry (TDR) methodology to detect wire sweep defect in nearly short condition - Ng, Kiong Kay (2023)
Wire sweep is a common defect observed in power semiconductor devices, especially when bonded with thin aluminium wire (< 100μm). The conventional methods for detecting the wire sweep defect are Automatic Optical Inspection (AOI), Real-Time X-ray and Automatic Test Equipment (ATE). However, all three methods are having capability limitations to detect the wire sweep defect, especially in nearly short conditions. The objective of this research is to develop a new test methodology to detect the wire sweep defect using Time Domain Reflectometry (TDR) that can overcome the limitations of these conventional methods. The focus of the wire sweep defects is on the wire-wire sweep and wire-lead sweep. The research is using power semiconductor device bonded with 75μm thin aluminium wire as test samples and consists of three experiments and a case study. The first experiment is to select the optimal TDR probe measurement methods that can be used to detect wire-related failure in a power semiconductor device. The second experiment is to study whether TDR can detect and respond when there is a wire sweep failure in the power semiconductor device. The last experiment is to characterize the response of the TDR curve with a statistical data analysis method and establish modelling with regression equations that can be used to predict the gap between the two wire sweeps. Lastly, a case study is performed to confirm that the proposed TDR methodology can detect the wire sweep defects and the gap for the wire sweep can be estimated using the regression equation model. By performing TDR measurement using Single-Pin Grounded method at the affected pin of the power semiconductor having a wire sweep defect and calculating the area under the TDR curve with a 4pSec time-range, the TDR curve shifts statistical significantly (p-value ≤ 0.05) to lower impedance in comparison to a good reference curve. This demonstrates that the proposed method using TDR can detect and respond to both types of wire-wire (WW) sweep and wire-lead (WL) sweep defects. By fitting the value for the area under the TDR curve into the regression equation established, the estimated gap between the wire sweep is within +/-10% tolerance in comparison to the actual gap. From this research, it is demonstrated TDR can detect both wire sweep defects in nearly short conditions on a power semiconductor device bonded with thin aluminium wire; and can overcome the limitation of conventional methods using AOI, X-ray and ATE electrical test. The area under the TDR curve together with the regression equation model can be used to predict the gap between wire sweep which is useful since it is a non-destructive method.